(untitled) (Fiep Bulletin - online, 2013)
The leprosy is mentioned in one of the older chineses agreement and brings historically an enourms load of prejudice (OPROMOLLA, 2000). The present study has as goal to evaluate the inlfuence of the trainings of leprosy in the increase of the detection of the disease in the State of Rio Grande do Norte. It is treat of a quantitative study accomplished in the hall municipal districts of the regionals of health and in Natal, selected because they were places of trainings in clinic of leprosy and their geographic positions would allow a big territorial inclusion of the State. These municipal districts have 10 or more teams of PHF, what is considerated important for the purposes of this study. The doctors and nurses who acts in the teams of PHF and who belong to the seven municipals districts selected constituted the population of study. The representation of each municipal district were based in the proportion that it contributed for the population of the teams. The route of the interview used as instrument has closed and open questions destined to obtain the perceptions of the professionals regarding of the training in clinic of leprosy, accomplished by the CLP-RN. The data collect were accomplished in the period from July 4th 2007 to April 14th 2008, after to receive an opinion favorable from the Ethics Committee of the Federal University of Rio Grande do Norte. The quantitative analysis were accomplished through the EPI INFO program, version 3.4.3. It was observed that there was an increase of leprosy detection, mainly in the period which happened most of the trainings in the researched municipal districts. It is observed that leprosy trainings had fundamental importance to the increase of detection and that starting from the professional qualification it can identify and to treat new cases of leprosy in a precocious way.